Diversity among maize landraces in North West Himalayan region of India assessed by agro-morphological and quality traits - Kumar, A.; Kumari, J.; Rana, J.C.; Chaudhary, D.P.; Kumar, R.; Singh, H.; Singh, T.P.; Dutta, M. (The Indian Journal of Genetics and Plant Breeding, 2016)
Fifty-one accessions collected from remote areas of NWH region (Himachal Pradesh and Jammu and Kashmir) were evaluated for genetic diversity on the basis of phenotypic and grain quality data. Significant differences were found among accessions for agro-morphological as well as quality traits.These accessions had relatively greater variability for yield per plant (g), grain weight (g), plant height (cm), ear height (cm), kernel rows, number of kernels per row, leaf width (cm) and tryptophan content. The cluster analysis based on the phenotyping and biochemical data divided 51 accessions into four clusters; all accessions from Jammu and Kashmir region grouped into cluster 1. Principal component analysis revealed that plant height, ear height, protein, oil, sugar, starch contents and leaf length (cm) were major contributor towards diversity. The grouping pattern obtained in the cluster analysis and PC biplot was congruent with geographical relationship among the accessions. Accessions such as IC556421 with high protein (13.27%) and sugar (4.53%) content, IC568267 with high oil content (4.94%) and IC568265 with high tryptophan content (0.56%) could be utilized in future research programme.